Local Wisdom in Learning: Ethnopedagogical Values of "Kandas" in Traditional Culinary Practices of the Ngaju Dayak Tribe - Franciska, Holla; Artika, I Wayan (Jurnal Paedagogy, 2026)
This study aims to describe and analyze the ethnopedagogical values embodied in the kandas culinary tradition of the Dayak Ngaju people. The research employed a qualitative approach using a descriptive ethnographic method. Data were collected through participatory observation, documentation, and in-depth interviews with traditional leaders, community leaders, the owner of a Dayak traditional restaurant, and members of the younger generation. The data were analyzed qualitatively using a cultural ethnographic approach with an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The analysis process was conducted iteratively and concurrently with data collection until the completion of the study. The findings indicate that the kandas culinary tradition embodies several ethnopedagogical values, including religious and spiritual values, togetherness, independence, environmental conservation, cultural identity, and intergenerational knowledge transmission. These values are highly relevant for integration into contextual learning grounded in local culture. This study contributes to the strengthening of local wisdom–based education and supports efforts to preserve the cultural heritage of the Dayak Ngaju community.